(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The aim of the current research is to identify (statistical thinking skills included in the mathematics books prescribed for the intermediate stage for the academic year 2021-2022 AD). Intermediate stage mathematics books (C1, C2) and there are (3) mathematics books for the academic year (2021-2022 AD), and the idea unit (explicit, implicit) was adopted as a unit for analysis, and repetitions as a unit for counting, and to achieve the goal of the research, the researcher built a preliminary list of statistical thinking skills, The apparent validity of the tool was confirmed by presenting it to a group of arbitrators, and the final list included (40) indicators and (26) sub-skills distributed over (4) main skills for statistical thinking. The researcher analyzed mathematics books for the intermediate stage using the content analysis tool (skills). Statistical thinking), the validity of the analysis, and the stability of the analysis were confirmed by both methods over time (the researcher with herself after a certain period of time), and through others (the researcher with other analysts), and the percentage of agreement was calculated using the Holsti equation, and the researcher used the Cooper equation ) and frequencies and percentages as statistical means. The research reached results, the most important of which is that the mathematics books prescribed for the intermediate stage included all the statistical thinking skills, but in varying proportions and in an unbalanced way. on the intermediate stage, in proportion to the scientific level of the subject, and taking into account the diversity in the selection of topics and exercises), and suggested conducting analytical studies of middle school mathematics books according to statistical thinking skills and the extent to which students acquired them, conducting descriptive studies to find out the extent to which learners possess statistical thinking skills and for different educational stages) .Keywords: statistical thinking, statistical thinking skills, middle school mathematics books.